2017
DOI: 10.1111/ceo.13085
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world visual outcomes in patients with neovascular age‐related macular degeneration receiving aflibercept at fixed intervals as per UK licence

Abstract: Patients in the real-world receiving aflibercept for nAMD at fixed intervals as per UK licence could achieve similar visual improvement at 1 year compared with phase III clinical trials. Undertreated patients had worse visual outcomes. Measures need to be introduced to increase clinic capacity and closely follow non-attenders to improve future outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Aflibercept has also been evaluated with several treatment regimens. 8 , 23 , 24 In the VIEW studies, monthly and bimonthly aflibercept treatment after 3 loading doses resulted in 8-9 letters of visual increase at month 12. 8 Yamamoto et al 25 evaluated the efficacy of treat-and-extend regimen with aflibercept in nAMD and demonstrated 1.5 lines of visual increase at month 12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aflibercept has also been evaluated with several treatment regimens. 8 , 23 , 24 In the VIEW studies, monthly and bimonthly aflibercept treatment after 3 loading doses resulted in 8-9 letters of visual increase at month 12. 8 Yamamoto et al 25 evaluated the efficacy of treat-and-extend regimen with aflibercept in nAMD and demonstrated 1.5 lines of visual increase at month 12.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these and other randomized controlled studies, the mean injection number during the first year was reported as at least 8. 6 , 8 , 12 , 23 , 24 , 25 On the other hand, reaching this injection number seems nearly impossible with the PRN treatment regimen in real life. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Most of the retrospective real-life studies reported the injection number as 3-4 during the first year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of electronic medical records (EMR) has facilitated the collection of large amounts of data in routine clinical practice and thus has the potential to make retrospective study populations more representative of real life. (13)(14)(15)(16)(17)(18) were merged into the current centralised repository, the data warehouse. We have created a dataset from this which represents, to our knowledge, the largest single-center cohort of patients receiving treatment for neovascular AMD in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of electronic medical records (EMR) has facilitated the collection of large amounts of data in routine clinical practice and thus has the potential to make retrospective study populations more representative of real life. (13)(14)(15)(16)(17)(18) This is very much dependent, however, on the quality of data entry and the reliable follow-up of patients, and so these issues can remain problematic. The amount of data available from EMR systems also challenges the traditional methods of validation, analytics and reporting, and there is a struggle to implement the existing clinical research guidelines.…”
Section: Introductionmentioning
confidence: 99%